ØªØ·ÙˆÙ‘Ø± Ø¯Ø±Ø§Ø³Ø© Ø¹Ù„Ù… Ø§Ù„Ø¨Ù„Ø§ØºØ© ÙÙ‰ Ø§Ù„Ø¹ØµØ±ÙŠÙ† Ø§Ù„Ø¬Ø§Ù‡Ù„Ù‰Ù‘ ÙˆØµØ¯Ø± Ø§Ù„Ø¥Ø³Ù„Ø§Ù… - Farohidy, Atiq (LISANIA: Journal of Arabic Education and Literature, 2018)
This study aims to determine the historical process that took place in the development of the history of Balaghah science. As is known that in the three Balaghah (Bayan, Badi 'and Ma'ani) sciences that have now arrived at us, have gone through the stages of evolution and dynamics. In the beginning, this knowledge emerged along with the emergence of the Arabic sciences which developed over centuries. This research is a qualitative research study using the literary study method in the process of collecting data sources. The results of this study indicate that during the Jahiliyah the Arabs had achieved high intellectual abilities in the knowledge of Balaghah and Bayan. This has been described in the Qur'an at the beginning of the surah ar-Rahman. Such a situation developed after the emergence of Islam. The development of Balaghah science began to appear in the time of the Umayyads and later developed after the sciences of poetry during the time of the first Abbas. Such things developed rapidly after Abdul Qahir established the Ma'ani theory of knowledge and the knowledge of Bayan.